2009
DOI: 10.1124/dmd.109.028225
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N-Terminal Domain Histidine and Proline Residues on the Substrate Selectivities of Human UDP-Glucuronosyltransferase 1A1, 1A6, 1A9, 2B7, and 2B10

Abstract: ABSTRACT:An N-terminal domain histidine [corresponding to position 39 of UDP-glucuronosyltransferase (UGT) 1A1] is conserved in all UGT1A and UGT2B subfamily proteins except UGT1A4 (Pro-40) and UGT2B10 (Leu-34). Unlike most UGT1A and UGT2B xenobioticmetabolizing enzymes, UGT1A4 and UGT2B10 lack the ability to glucuronidate 4-methylumbelliferone (4MU) and 1-naphthol (1NP), both planar phenols, and naproxen (a carboxylic acid). However, only UGT1A4 glucuronidates the tertiary amines lamotrigine (LTG) and trifluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…1, lane 4) that was devoid of glycosidation activity. The UGT3A2del-exon2 variant is missing all 34 amino acids of exon 2, including His35, the presumptive catalytic base required for catalysis (Kubota et al, 2007;Kerdpin et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…1, lane 4) that was devoid of glycosidation activity. The UGT3A2del-exon2 variant is missing all 34 amino acids of exon 2, including His35, the presumptive catalytic base required for catalysis (Kubota et al, 2007;Kerdpin et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…9). It is likely that they failed to catalyze this N-glucuronidation reaction because they have a His residue at the "catalytic His" position, position 39 of the protein precursor sequence (Li and Wu, 2007), while the human UGT1A4 has a Pro residue at this position (Kerdpin et al, 2009). It may be further suggested that both medetomidine enantiomers are glucuronidated in the dog by one or two UGTs of family 2, particularly if an equivalent of the human UGT2B10 is present there (Kaivosaari et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic residues of the UGTs, a histidine at the beginning of N␣1 and an aspartate at the end of N␤4, have been addressed in several studies Patana et al, 2008;Kerdpin et al, 2009). In UGT1A1, either Asp146 or Asp151 could be the critical acid.…”
Section: Tablementioning
confidence: 99%